2022
DOI: 10.3390/joitmc8030109
|View full text |Cite
|
Sign up to set email alerts
|

Trust and Loyalty in Building the Brand Relationship with the Customer: Empirical Analysis in a Retail Chain in Northern Brazil

Abstract: The purpose of this article is to analyze the relationship between a brand’s trust in consumer decisions and its maintenance over time in a retail chain in northern Brazil known as Bemol. The sample consists of 210 respondents, customers of Bemol, and the methodology used is a model of structural equations. The developed model consists of 22 variables, divided into three constructs: trust, loyalty and brand. The results show the importance of trust in the consumption decision, as well as loyalty, relationship … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 71 publications
1
4
0
1
Order By: Relevance
“…However, it is worth noting that a majority of respondents (31.4% agree and 51.0% strongly agree) perceive their respective hospitals as enjoying a high level of customer trustworthiness. This indicates a positive reputation and a strong sense of trust among customers towards the organization, consistent with the assertion made by Cardoso et al (2022), emphasizing the significance of trust in fostering loyalty and confidence in the organization's ability to effectively meet customer needs.…”
Section: Application Of Focus Leadership Strategysupporting
confidence: 84%
“…However, it is worth noting that a majority of respondents (31.4% agree and 51.0% strongly agree) perceive their respective hospitals as enjoying a high level of customer trustworthiness. This indicates a positive reputation and a strong sense of trust among customers towards the organization, consistent with the assertion made by Cardoso et al (2022), emphasizing the significance of trust in fostering loyalty and confidence in the organization's ability to effectively meet customer needs.…”
Section: Application Of Focus Leadership Strategysupporting
confidence: 84%
“…D and Kara. A revealed that the existence of brand trust abated consumer discomfort, affected consumer cognition, emotions, and behavior toward the brand, and promoted purchase decisions [ 47 ]. The augmentation of consumer awareness regarding the brand instills a sense of tranquility and contentment in the user, thereby reducing the perceived distance between the brand and the consumer.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…Trust has a key role in the field of marketing in maintaining and developing the relations between the ones participating in an exchange process, in particular, in the buyer-seller relations developed to acquire a service/product (Sarwar et al , 2012). Trust plays a crucial role in shaping customers' intentions, as it helps businesses establish and retain their loyalty (Cardoso et al , 2022; Guenzi et al , 2009). When consumers have faith in a company, they anticipate that the company will fulfill its commitments as advertised.…”
Section: Literature Reviewmentioning
confidence: 99%